Modelling of Ambient Comfort Affect Reward Based Adaptive Laboratory Climate Controller - Bielskis, A. A.; Guseinoviene, E.; Drungilas, D.; Gricius, G.; Zulkas, E. (Elektronika ir Elektrotechnika, 2013)
There are enlarged capabilities of the Ambient Comfort Affect Reward Based Laboratory Climate Controller (ACAR-Controller) by developing and integrating of the Heating/Ventilation/Air Conditioning (HVAC) and the Red-Green-Blue-Yellow (RGBY) Light Emitting Diode (LED) lighting sub-models of one room laboratory in the ACAR-Controller model. The model was validated by implementation and testing of the following elements of the laboratory prototype of ACAR-Controller: a) the sustainable electric power distribution subsystem; b) the intelligent RGBY LED lighting subsystem; c) the non-invasive measuring subsystem of human reaction to comfort conditions in the laboratory; d) the ATMEGA128RFA1-ZU transceivers based wireless communication subsystem; e) the software for the ACAR-Controller. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5399